Effect of Rate and Sources of Nitrogen, Phosphorus and Zinc Fertilization on Potassium Nutrition of Rice in Different Cultivation Methods - Shahane, Amit Anil; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2018)
A field study was conducted in 2013–14 and 2014–15 at Research Farm of ICAR-Indian Agricultural Research Institute, New Delhi, India with the objective to quantify variation in concentration and uptake of potassium (K) as influenced by rate and sources of nitrogen (N), phosphorus (P) and zinc (Zn) in rice. The rate of nutrient application (N and P) had strongly significant effect, followed by cultivation methods and least in case of Zn fertilization on concentration and uptake of K in rice. Among concentration and uptake, uptake was more affected due to applied treatments; while among growth stages, effect was significant at 70 and 100 days after sowing and in straw and milled rice. Application of recommended dose of N and P (RDN) increased total K uptake by 10–12 and 27–28 kg ha-1 over 75% RDN and control, respectively. Increase in total K uptake in puddled transplanted rice (PTR) and system of rice intensification (SRI) was 11–13 and 12–13 kg ha-1 over aerobic rice system (ARS). Similarly, increase in uptake due to application of microbial inoculations (MI) and Zn fertilization was 8–14 and 3–7 kg ha-1. Soil available K showed negative balance which indicates that higher uptake than K applied through fertilizer and need of K fertilization in rice. Our study designates superiority of SRI and PTR among cultivation methods and RDN+Zn and 75% RDN+MI+Zn within nutrient management options in K nutrition of rice.